A Challenging Colectomy for Acute Severe Ulcerative Colitis Complicated by COVID-19. Issue 10 (6th July 2020) - Di Ruscio, Mirko; Variola, Angela; Angheben, Andrea; Resimini, Silvia; Geccherle, Andrea; Ruffo, Giacomo; Barugola, Giuliano
Abstract : We present the case of a patient with acute severe ulcerative colitis and concomitant COVID-19-related pneumonia who required a colectomy after a prolonged and complicated hospitalization during the initial stages of the SARS-CoV-2 pandemic, before the establishment of official procedures.